Investigating the prudential determinants of infrastructural investment appraisal techniques in airports company South Africa - Ndadza, Phindulo (Graduate School of Business (GSB), 2025)
Academic literature advocates that infrastructure contributes significantly to a country's economic development. In the South African context, airport infrastructure is one of the contributors to the economic development of the country. The South African government has limited financial resources, to service public infrastructural needs; therefore, the national government implemented the Sustainable Infrastructure Development Symposium [SIDSSA] initiative on 23 June 2020 to accelerate the delivery of country infrastructure. However, project appraisal was identified as a key governmental challenge - particularly in the public investment management space - and many projects were funded prematurely. This perspective has motivated a host of academic literature to analyse airport infrastructure investment decision making process, based on financial and non-financial factors. Consequently, this current research was conducted, using an exploratory qualitative methodology, to explore the appraisal techniques mostly used in infrastructure investment decision making at the Airport Company South Africa [ACSA]; determinants of infrastructural investment decision making; and to make recommendations for prudential infrastructural investment appraisal techniques for ACSA. The primary data was collected from 10 ACSA senior and professional employees, both current and previous members of investment committees. The findings concur with academic literature, which identify the best infrastructural investment appraisal techniques as Net Present Value and Internal Rate of Return, the appraisal techniques that assess the time value of money, specifically, receiving a rand today is more valuable than receiving a rand in the future, due to uncertainties. Additionally, the study revealed that ACSA needs to consider both financial and non-financial factors when making an investment decision, namely, alignment with company strategy, compliance with regulations and standards, project lifecycle, sustainability, project value, financial position, and competitive advantage. Ultimately, as a result of this current study, the research recommends that the ACSA management do not deviate from their current appraisal techniques. However, ACSA needs to enhance the investment decision making process, by using external project valuators for Confidential Confidential selected projects. Additionally, it is recommended that ACSA offer investment management training courses timeously; conduct a random independent review on project risk, introduce an audit, to inspect if the investment decision process is not contributing to inefficiency; and lastly, pursue several less regulated infrastructural projects, such as warehouses, lounges, hotels, office space, retail stores, and parking lots, especially those projects in the airport landside, compared to airside infrastructure projects, accommodating aircraft movement.